(ISC)2 CCSP Certified Cloud Security Professional Official Study Guide - Malisow, Ben (New York : Wiley, 2020)
Describes spectacular and interesting animal traits, including how draco lizards glide, how electric eels make electricity, and how snakes smell with their tongues.--
Contact to Central Library: library@iittp.ac.in
Keywords: Computing and Processing; General Topics for Engineers; Cloud Security